Validez concurrente de cinco ecuaciones de predicción para evaluar el porcentaje de grasa en un grupo de deportistas con proyección al alto rendimiento de la ciudad de Medellín - Colombia. - Lucía López, Ana; David Vélez, Juan; María García, Angélica; Fernando Arango, Elkin (Revista Biomedica, 2021)
Introduction: In Medellín, Colombia, there are no equations to predict the body composition (BC) of athletes expected to have high performance, making it difficult to make decisions related to training and nutrition plans. Objective: To calculate the concurrent validity of five prediction equations for fat percentage (FP) within a group of athletes from the city of Medellin, Colombia expected to yield high performance. Materials and methods: Cross-sectional analysis for diagnostic tests validation with data from a secondary source of athletes under the age of 18 who were part of Team Medellín. The "gold standard" was dual-energy X-ray densitometry (DEXA); the prediction equations analyzed included: Slaughter, Durnin and Rahaman, Lohman, Johnston, and the Five-Component method. The ICC was used to assess the consistency between the methods; moreover, the Bland-Altman plot was used to calculate the average bias and agreement limits of each of the equations. Results: Participation included 101 athletes (50,5% women), the median age being 14,8 years old (IR 13,0 to 16,0). The concurrent validity was "good/excellent" for the Johnston, Durnin and Rahaman and Five Components equations. The Lohman equation, which overestimated the FP in 12,7 percentage points. All of them showed broad agreement limits. Conclusions: For the study population, the Durnin and Rahaman, Johnston and Five- Component equations can be used to predict the FP because they yield a "good/excellent" concurrent validity and a low average bias. The equations analyzed have low accuracy, making it difficult to use them to diagnose the individual FP within this population.